Pengaruh Lingkungan Kerja Fisik terhadap Kinerj Karyawan pada Kantor Badan Penanggulangan Bencana Daerah Kabupaten Batanghari - Mella Sary (Science of Management and Students Research Journal (SMS), 2021)
The purpose of this study is as follows: 1.) To find out and describe the work environment and employee performance at the office of the Regional Disaster  Management Agency of Batanghari Regency. 2.) To analyze the influence of the physical work environment on employee performance in the office of the regional disaster management agency of Batanghari regency. The type of data required and collected in this study is quantitative data. The object of this research is Office of the Regional Disaster Management Agency Of Batanghari Regency. Sources of data in this study are Office of the Regional Disaster Management Agency Of Batanghari Regency., and Questionnaires and respondents to the office of the Batanghari district disaster management agency. Based on the resuts of the study obtained linear regression value that is Y = 1.518 + 0.511 X, with a value of R and a R2 value of 0.238 in the test t work environment affects employee performance in the office of the regional disaster management agency with a value of 3.447 and a significant value of 0.001.The conclusion in this study is that the physical work environment significantly affects employee performance in the office of the Regional Disaster Management Agency of Batanghari district this is evidenced by a significant value of 0.001<0.05 results coefficient of determination of 23.8% show the value of employee performance is influenced by the remaining physical work environment of 76.2% the value of employee performance is influenced or explained by other factors that are not studied. By this researcher.